Thermodynamic, environmental, and exergoeconomic feasibility analyses and optimization of biomass gasifier-solid oxide fuel cell boosting a doable-flash binary geothermal cycle; a novel trigeneration plant. (15th February 2023) - Hou, Rui; Zhang, Nachuan; Gao, Wei; Chen, Kang; Liu, Yongqiu
Abstract: Heat recovery boosting applications, especially polygeneration, provide an efficacious effort toward sustainable energy supply, air pollution control, and financial saving. Among new technologies, solid oxide fuel cells are able to effectively operate benefiting from high-temperature syngas output to boost the applicability of combined cycles. Respecting this manner and embracing a renewable energy resource, i.e., biomass fuel, a biomass Gasifier-Solid oxide fuel cell is devised in this paper; its waste heat is recovered by a doable-flash binary geothermal power plant for better operation. Accordingly, a thermal-based desalination, namely humidification dehumidification desalination, and a domestic water heater are joint to the geothermal cycle resulting in a novel trigeneration application. The possibility is measured by thermodynamic, environmental and exergoeconomic tools; a comprehensive sensitivity analysis is applied together with a multi-objective grey wolf optimization in three different optimization scenarios. Considering eight decision variables for the sensitivity analysis and optimization, the optimization scenarios comprise exergetic efficiency/sum unit cost of products, exergetic efficiency/levelized total emission, and exergetic efficiency/hot water production. Here, the last scenario possesses the best optimum exergetic efficiency of 64.49%; the optimum sum unit cost of product, levelized total emission, and heating production are forecasted at 4.94 $/GJ, 0.124 ton/MWh, and 6549.77 kW, respectively. Highlights: A novel power, heating, and freshwater trigeneration system is proposed. Geothermal and biomass energy sources are used to improve system performance. Thermodynamic, exergoeconomic, and environmental analyses are performed. Performing multi-objective grey wolf optimization in various optimization scenarios. The optimum exergetic efficiency and SUCP of 64.49% and 4.94 $/GJ are obtained.